Dishing on dinner: a life course approach to understanding the family meal context among families with preschoolers. Issue 6 (20th April 2021) - Walton, Kathryn; Breen, Andrea; Gruson-Wood, Julia; Jewell, Kira; Haycraft, Emma; Haines, Jess
Abstract: Objective: Family meals promote healthful dietary intake and well-being among children. Despite these benefits, family meal participation typically declines as children age. This study utilises life course theory to explore parents' perceptions of family meals in order to understand how parents' past experiences with family meals (in childhood and earlier in adulthood) influence their current beliefs and practices regarding mealtimes with their own children. Design: Semi-structured qualitative interviews. Setting: In-person interviews were conducted in participants' homes. Participants: Twenty families (twenty-one mothers and fifteen fathers) with a child aged between 18 months and 5 years. Results: Thematic analysis revealed that families seemed to primarily approach mealtimes from one of three overarching orientations: meals for (1) Togetherness, (2) Nutrition Messaging or (3) Necessity. These orientations were informed by parents' own mealtime experiences and significant life transitions (e.g. parenthood). The current family meal context, including the messages parents shared with their children during mealtimes and the challenges experienced with mealtimes, characterised the orientations and families' approaches to mealtimes. Conclusions: Parents' own early life experiences and significant life transitions influence why families eat meals together and have important implications for the intergenerational transmission of mealtime practices. Results may help to inform the content and timing of intervention strategies to support the continuation of frequent family meals beyond the preschool years.